Prophylactic clipping not effective in preventing post‐polypectomy bleeding for < 20‐mm colon polyps: A multicenter, open‐label, randomized controlled trial. Issue 2 (29th July 2020) - Inoue, Takuya; Ishihara, Ryu; Nishida, Tsutomu; Akasaka, Tomofumi; Hayashi, Yoshito; Nakamatsu, Dai; Ogiyama, Hideharu; Yamaguchi, Shinjiro; Yamamoto, Katsumi; Mukai, Akira; Kinoshita, Kazuo; Yakushijin, Takayuki; et al.
Abstract: Background and Aim: Prophylactic clipping (PC) after polypectomy has the potential to prevent post‐polypectomy bleeding (PPB). We aimed to evaluate the effectiveness of PC in preventing PPB for < 20‐mm polyps. Methods: This multicenter, open‐label, randomized controlled trial conducted from December 2013 to June 2017 at 10 institutions randomly assigned 1080 patients with < 20‐mm colon polyps to the non‐PC and PC groups. Allocation factors were institution, antiplatelet drug use, and polyp number. The primary endpoint was differences in PPB rates between the groups. The severity of PPB and post‐procedural abdominal symptoms were also investigated. These endpoints in intention‐to‐treat and per‐protocol (PP) analyses were evaluated. Results: We investigated 1039 patients with 2960 lesions. There was no significant difference between the groups in characteristics including age, sex, hypertension, diabetes, hyperlipidemia, antiplatelet drug use, and lesion characteristics such as type and size. Excluding the clip used in the non‐PC group, intraoperative bleeding, and deviation of protocol, 903 patients were investigated in PP analysis. There was no significant difference in the PPB rate between the non‐PC and PC groups (2.7% vs 2.3%, P  = 0.6973 [intention‐to‐treat analysis]; 3.0 vs 2.4%, P  = 0.7353 [PP analysis]). Severe PPB (≥ grade 3) was similar between the groups. Total procedure time was significantly shorter in the non‐PC group than in the PC group (31 vs 36 min, P  = 0.0002). Post‐procedural abdominal fullness was less common in the non‐PC group than in the PC group (20.8% vs 25.6%, P  = 0.0833). Conclusion: Prophylactic clipping is not effective in preventing PBB for < 20‐mm colon polyps (UMIN000012163).